Babymouse tales from the locker presents lights, camera, messy whiskers - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2017)
"Babymouse joins the school Film Club and writes the greatest cinematic masterpiece of all time! But when the movie gets shown to the entire school, will it be a box office hit or a flop?"--